2020
DOI: 10.3390/agriculture10120577
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Environmental Characteristics and Risk Management Practices on Produce Farms: A Systematic Literature Review

Abstract: Produce-associated foodborne disease outbreaks have increased worldwide highlighting the importance of proper implementation of risk management practices (RMP). We determined the relationship between environmental characteristics (i.e., physical resources) of produce farms and implementation of RMP. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses principles, we identified 36 studies to include in our analysis. Most study data were collected through surveys administered to growers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Borehole water is generally of better quality than well water and may require minimal treatment before consumption [16] . The depths of boreholes in Nsukka range from 50 to 240 m [17] .…”
Section: Materials and Methods 21 Description Of The Study Areamentioning
confidence: 99%
“…Borehole water is generally of better quality than well water and may require minimal treatment before consumption [16] . The depths of boreholes in Nsukka range from 50 to 240 m [17] .…”
Section: Materials and Methods 21 Description Of The Study Areamentioning
confidence: 99%
“…This systematic review was conducted following the PRISMA principles [22], and we referred to several other systematic reviews [23][24][25][26]. Web of Science and PubMed were selected as the scholarly online databases.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-six of the thirty-seven reports showed an association between Ca deficiency and/or Ca accumulation and the expression of Ca 2+ -movement-related genes (Ca 2+ antiporters [27,29,32,35,36,39,[42][43][44][45][46][47][48][49][50]53], calreticulin [30,[51][52][53], Ca 2+ -ATPase [35,36,39,54,55], Ca 2+ channels [55][56][57][58], and PME [35,59]). Of the remaining studies, five studies identified QTLs that described variation in tipburn incidence [25,26,33,34,38]. Two studies investigated the causative genes of Ca deficiency disorders and Ca accumulation by focusing on morphological traits (leaf shape [28] and root hair production [61]).…”
Section: Synthesizing Current Knowledge Regarding the Role Of Gene Expression In The Occurrence Of Ca 2+ Deficiency Disordersmentioning
confidence: 99%